Skin Temperature After Interscalene Brachial Plexus Blockade. Issue 6 (1st November 2007) - Hermanns, Henning; Braun, Sebastian; Werdehausen, Robert; Werner, Andreas; Lipfert, Peter; Stevens, Markus F.
Abstract : Background and Objectives: In neuraxial anesthesia, increase of skin temperature is an early sign of successful block. Yet, during peripheral nerve block of the lower extremity, increase in skin temperature is a highly sensitive, but late sign of a successful block. We hypothesized that after interscalene brachial plexus block, a rise in skin temperature follows impairment of sensation during successful nerve block and occurs only distally, as observed in the lower extremity. Methods: In the present study, we prospectively evaluated the changes in skin temperature after interscalene brachial plexus blockade in 45 patients scheduled for elective shoulder surgery. We assessed pinprick and cold sensation as well as skin temperature at sites of the skin innervated by the median, ulnar, radial, axillary and musculocutaneous nerve. Results: At the skin areas innervated by the axillary and musculocutaneous nerve, skin temperature did not increase after successful block. At the distal sites, innervated by the median, ulnar, and radial nerve, skin temperature increased significantly (1.9-2.1°C within 30 min) after successful block while it did not after failed nerve block or on the contralateral side. In these areas attenuation of skin sensation preceded a measurable rise in skin temperature (≥1°C) in 56.3% of nerve blocks, occurred at the same time in 35.2%, and in 8.5% the temperature rise occurred first. Conclusions: Assessment of skin temperature cannot predict the success of an interscalene brachial plexus block of the axillary and musculocutaneous nerve. Distally, the increase of skin temperature has a high sensitivity and specificity but occurs later than the loss of sensory and motor functions. Therefore, the measurement of skin temperature during interscalene blockade is of limited clinical value.